The Classification of The Turkic And Uzbek Proverbs - Mirzaahmedov Mirjalol Mansurjon ugli (Web of Journals Publishing, 2023)
This article is of an overview nature of Turkic languages and their classification. Some old and modern ideas about the development of the Turkic languages are addressed. Special attention is paid to the issue of classification of Turkic languages. Turkic languages are historically primordial commonalities that evolved from the common grammatical structure and vocabulary of the languages of the earlier communities of primitive communal clan associations.
Keywords: Turkic languages, western Hunnu, eastern Hunnu, Oguz, Kipchak, Turkic (Uigur), scheme of Turkic language